Getting started in endoscopic ear surgery - Peter Ryan; Carolina Wuesthoff; Nirmal Patel (中华耳科学杂志（英文版）, 2020)
Endoscopic ear surgery (EES) is an exciting, rapidly developing and innovative field of otologic surgery. Technically and conceptually, EES is a significant departure from traditional microscopic transcanal ap-proaches to the middle ear and canal that has shown very positive results with respect to patient out-comes. This review serves as a primer for the otologist and otology resident embarking on EES and discusses the theory surrounding the learning process, the optical chain for endoscopic surgery as well as other important underlying principles.